DETERMINATION OF URBAN SPRAWL PHENOMENON IN PEKALONGAN CITY AND ITS SURROUNDING - Fatimah, Endrawati; Anwar, Aris Choirul (Diponegoro University, 2023)
Urbanization defines as a spatial and socio-economic transformation process from rural to urban areas. While urban sprawl is the process of propagation of the appearance of urban physical characteristics from the inner city toward the urban fringe area. Pekalongan City has grown from a small town to a medium-sized city with a population of 300,000 people. This study aims to identify the phenomenon of urban sprawl in Pekalongan City and its surroundings (Pekalongan and Batang Regency) and identify the urban environment quality based on the condition of the public services availability in these urban areas. The data used in this study were the 2019 Village Potential (PODES) from the Central Agency on Statistics (BPS) and a digital base map from the Geospatial Information Agency (BIG). The urban-rural classification scoring from the BPS was used to identify urban areas as the method in this study. The results showed that 111 out of 285 villages in Pekalongan Regency and 63 out of 248 villages in Batang Regency could already be classified as urban areas and formed an urban agglomeration with Pekalongan City. This study also showed that the environmental quality in urban areas with urban sprawl phenomenon has met the standards and criteria for urban public services compared to other areas.